2020
DOI: 10.5194/bg-17-1583-2020
|View full text |Cite
|
Sign up to set email alerts
|

Carbon–nitrogen interactions in European forests and semi-natural vegetation – Part 1: Fluxes and budgets of carbon, nitrogen and greenhouse gases from ecosystem monitoring and modelling

Abstract: Abstract. The impact of atmospheric reactive nitrogen (Nr) deposition on carbon (C) sequestration in soils and biomass of unfertilized, natural, semi-natural and forest ecosystems has been much debated. Many previous results of this dC∕dN response were based on changes in carbon stocks from periodical soil and ecosystem inventories, associated with estimates of Nr deposition obtained from large-scale chemical transport models. This study and a companion paper (Flechard et al., 2020) strive to reduce uncertaint… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 152 publications
(249 reference statements)
1
24
0
Order By: Relevance
“…None of the commonly accepted eutrophication indicators mentioned above apply to all plots. This conclusion is confirmed by [ 73 ]. It must be stated that the confidence interval for the relation between N leaching and N deposition becomes very lager at higher N inputs due to the different site conditions with respect to soils and climate.…”
Section: Discussionsupporting
confidence: 85%
“…None of the commonly accepted eutrophication indicators mentioned above apply to all plots. This conclusion is confirmed by [ 73 ]. It must be stated that the confidence interval for the relation between N leaching and N deposition becomes very lager at higher N inputs due to the different site conditions with respect to soils and climate.…”
Section: Discussionsupporting
confidence: 85%
“…3 . Because of the large numbers of atmospheric N species and their complex atmospheric chemistry, quantifying the deposition of N r is hugely complex and is a key source of uncertainty for ecosystem effect assessment (Bobbink et al, 2010;Fowler and Reis, 2007;Schrader et al, 2018;Sutton et al, 2007). Input by dry deposition can be estimated using a combination of measured and/or modelled concentration fields with high-resolution inferential models (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that root mean square error (RMSE) was 4.4 m and R 2 was 0.7 after removal of seven outliers. For the FLUXNET forest sites used in this study, we compared the forest canopy heights from GLAS to the maximum forest canopy height at the FLUXNET sites taken from (Flechard et al, 2020). For all but one site (DE-Hai), the forest canopy heights from GLAS were lower than this value (Table S3).…”
Section: Discussionmentioning
confidence: 99%
“…The nitrogen (N) cycle has been continuously disrupted by human activity over the past century (Fowler et al, 2015;Galloway et al, 2004Galloway et al, , 2008, resulting in a doubling of the total reactive nitrogen (N r ) fixation globally and even a tripling in Europe. As a result, excessive amounts of N r , defined as all N compounds except N 2 , have manifested in the environment contributing to acidification and eutrophication of sensitive terrestrial and aquatic ecosystems (Bobbink et al, 2010a;Paerl et al, 2014).…”
mentioning
confidence: 99%
See 1 more Smart Citation